Strategi Optimalisasi Pendapatan Asli Daerah Melalui Inovasi dan Kolaborasi di Kabupaten Lombok Tengah - Fathurrahman; Safitri, Julia; Munizu, Musran; Nasir (Jurnal Bina Praja, 2024)
This study discusses the condition of Regional Original Revenue (PAD) which consists oftax components, levies, results of separated regional assets and other revenues that are considered legitimate. In addition, this study emphasises the preparation of a strategy for optimising Regional Original Revenue (PAD) which emphasises innovation and collaboration so that the results and targets for increasing PAD in Central Lombok Regency can be achieved. the importance of innovation as a transformer and collaboration in building networks in Central Lombok Regency. This study uses a descriptive qualitative approach using some LKPD data for the last 5 years from 2019-2023. In addition, the method used in preparing the strategy is more result-oriented and more positive with the SOAR approach by analysing strengths, opportunities, aspirations and results while the study locus is Central Lombok Regency. This study found that one of the important steps in strengthening regional finances is the optimisation of local revenue through sustainable policies. Local governments can sustainably increase tax revenues, support regional development, and improve community welfare by using appropriate strategies and comprehensive policies. Annual growth rate, the average percentage of growth each year is 10.25%, the annual growth rate experienced negative PAD growth (-21%). Some strategies that can be developed in order to optimise PAD through innovation and collaboration are to create innovations in the local taxation and levy sector, both in terms of collection and recording. In addition, strengthening networks and collaboration with various parties will make it easier for the Central Lombok Regency Government to map potential sectors that can be utilised to increase PAD.